The price of success: Equal Pay and the US Women`s National Soccer Team - Culvin, A.; Bowes, A.; Carrick, S.; Pope, S. (Soccer & Society, 2022)
This commentary offers an analysis of the implications of the US Women` National team Collective Action lawsuit against the US Soccer Federation. The players filed the lawsuit based on two grounds: first, that the US Soccer Federation violated the Equal Pay Act by paying them less than the men`s national team and second, that the federation discriminated against them under Title VII of the Civil Rights Act 1964, specifically in regard to workplace conditions. In this article, we discuss three interrelated aspects: (1) the legal implications of either the success or failure of the dispute; (2) playing and workplace conditions; and (3) the gendered meanings of equal pay and its socio-cultural implications. These significant challenges require analysis to understand potential implications of the outcome for women`s football, and beyond. Recommendations are made for governing bodies and football clubs, in addition to possible future research directions for academics. We reflect upon the gendered, social and sporting meaning of equal pay for continuing the momentum of women`s football, highlighting the need for the most successful women`s football team in the world to achieve parity if we are to continue advancing gender equality in a `new age` of women`s sport.